Report: Visit To Copenhagen: 6-16 June 2001 - Valerie Ehlers (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences, 2001)
During this visit three international conferences were attended: · 12th International Nursing Research Conference (STTI) with the theme: Clinical scholarship, technology and globalization connects nursing scholarship with clinical practice around the globe · 3rd International Network for Doctoral Education in Nursing (INDEN) with the theme: The social relevance of nursing scholarship and doctoral education · 22nd Quadrennial International Council of Nurses (ICN) Conference with the theme: Nursing: a new era.